2021
DOI: 10.3390/sym13081447
|View full text |Cite
|
Sign up to set email alerts
|

Secure Surveillance Systems Using Partial-Regeneration-Based Non-Dominated Optimization and 5D-Chaotic Map

Abstract: Due to Internet of Things (IoT), it has become easy to surveil the critical regions. Images are important parts of Surveillance Systems, and it is required to protect the images during transmission and storage. These secure surveillance frameworks are required in IoT systems, because any kind of information leakage can thwart the legal system as well as personal privacy. In this paper, a secure surveillance framework for IoT systems is proposed using image encryption. A hyperchaotic map is used to generate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Tseng et al, [21] have introduced a model by proposing a group-based access structure and Cipher text-Policy Attribute-Based Encryption (CP-ABE) to cater to the issue of data confidentiality and access privacy over health data. Ghosh et al, [13] have demonstrated that neither the technique is efficient nor practically implacable.…”
Section: Review Of Authentication Schemes In Health Care Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tseng et al, [21] have introduced a model by proposing a group-based access structure and Cipher text-Policy Attribute-Based Encryption (CP-ABE) to cater to the issue of data confidentiality and access privacy over health data. Ghosh et al, [13] have demonstrated that neither the technique is efficient nor practically implacable.…”
Section: Review Of Authentication Schemes In Health Care Systemsmentioning
confidence: 99%
“…To ensure the confidentiality and privacy of patients' data, the proposed novel heterogeneous communication architecture provides a multifactor authentication policy. The proposed scheme exploits customized SDN and a framework [12][13][14] of body sensors coupled with IoT nodes, Cloud Analytics support for smart summarisation.…”
Section: Introductionmentioning
confidence: 99%
“…The role of forger bees is to constantly visit the food source to obtain nectar. Scout bees are those who conduct random searches to discover new sources of food [ 33 ]. The pictorial representation of the bees’ searching process of food is illustrated in Figure 7 .…”
Section: Proposed Workmentioning
confidence: 99%
“…Furthermore, usually enhancement algorithms rely on authentic parameter selection. This prompted a recommendation a robust enhanced Gabor filter by integrating it with various enhanced techniques such as gamma corrected adaptively with distributed weights (GCADW) [ 55 , 56 ], homomorphic filter [ 57 , 58 ], joint equalization of histogram (JEH) [ 59 , 60 ], unsharp masking filter, adaptive unsharp masking filter [ 61 , 62 ], and particle swarm optimization (PSO) based unsharp masking filter [ 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%